(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India is the second largest country in the world based on population and a major part of the population are depends on agricultural activities. Now a day the organic agriculture is improving very well. Organic agriculture is not a replacement concept in India. We are leading a hectic life these days. Due to the scarcity of our time, lifestyle changes, taste and preference changes, there has been an inclination towards conventional food products which are readily available in the supermarkets such as vegetables, fruits, dairy products meat products and so on. The beginning stage people were not concerned about the safety and quality of conventional or inorganic food products and the implications these conventional food products will have on their health. The present study is focused on consumer perception towards organic products and it has been carried out with the sample size of 120 represents who are familiar with organic products.